Differences in the salivary inorganic ions levels and salivary flow rate of the periodontitis and non-periodontitis patients - Amalina, Rizki; Mahdalena, Mahdalena; Aditya, Grahita (Universitas Padjadjaran, 2020)
Introduction: Saliva contains numerous proteins and electrolytes that may serve as biomarkers of pathological conditions, including periodontitis. Saliva flow also influenced by pathological conditions, such as periodontitis. Therefore, saliva analysis, as one of the biomarker source needs to be examined. This study was aimed to analyse the differences salivary inorganic ions levels (calcium, phosphate, and bicarbonate) and salivary flow rate in periodontitis and non-periodontitis patients. Methods: This research was analytic-observational using two groups, the healthy periodontal group consisting of 21 people (PI scores between 0-0.2) and the periodontitis group consisting of 21 people (PI scores between 0.7-8.0). Unstimulated saliva was collected using a passive drolling method. The calcium, phosphate and bicarbonate levels in the saliva were analysed using UV/Vis spectrophotometers. Results: Calcium, phosphate and bicarbonate levels in saliva were different between groups. Salivary flow rate also different between groups. There was a significant difference (p = 0.00) in the calcium, phosphate and bicarbonate levels between groups (t-test), and also significantly different (p = 0.000) salivary flow rate between groups. The higher the salivary flow rate, the higher the levels of calcium, phosphate and bicarbonate would be. Conclusion: Periodontitis condition increases the level of salivary inorganic ions and salivary flow rate because of periodontal inflammation. This inflammation mainly because of plaque deposition and calculus. Increased level of inorganic ions in the saliva such as calcium, phosphate, and bicarbonate, and also the salivary flow rate indicates the existence of a periodontal disease.